Muutos psykiatristen avohoitokäyntien toteutuksessa ja johtajien kokemukset etäasiointia estävistä ja edistävistä tekijöistä COVID-19 aikakaudella - Laukka, Elina; Gluschkoff, Kia; Kaihlanen, Anu-Marja; Suvisaari, Jaana; Kärkkäinen, Jukka; Vorma, Helena; Heponiemi, Tarja (Finnish Journal of eHealth and eWelfare, 2021)
Psychiatric outpatient care has been actively digitalized even before the COVID-19 outbreak. However, COVID-19 has increased the adoption of digital and remote health services. The aim of this cross-sectional study was to examine whether COVID-19 has impacted on the form of psychiatric outpatient services and describe psychiatric healthcare leaders’ experiences of digital and remote services. The results of this study can be used to evaluate and develop psychiatric outpatient services and to facilitate further research. The data was collected through an online survey after the COVID-19 outbreak in May 2020. The questionnaire contained structured and open-ended questions. A total of 39 adult psychiatric, youth psychiatric and pediatric psychiatric service leaders answered the survey from 19 different health care districts. Quantitative questions about the forms of psychiatric outpatient services were reported using percentages, whereas open-ended questions were analyzed using inductive content analysis. The results showed that the relative amount of digital and remote services increased after the COVID-19 outbreak. Of the psychiatric outpatient visits, 9 % were conducted using phone or remote access in January and 48 % in May (rose by 39 percentage units). The challenges for using remote services were related to the lack of IT equipment and inoperative programs, customers’ lack of devices, connections and room, remote services’ unsuitability for all operations, negative attitude of professionals and customers, insufficient IT knowledge, and organizational problems. The supporters of remote service usage were related to customers’ and professionals’ positive attitude and atmosphere, the necessity for the remote services caused by the COVID-19, suitability and familiarity of remote services in psychiatry, familiarity of the customers, long distances, well-functioning remote networks and time savings, functional technology, programs and devices, and sufficient support. Digital and remote services have enabled psychiatric outpatient services to those patients for whom they are suitable and who can use them. The importance of digital and remote services in the era of COVID-19 epidemic has been important, but it is important to innovate other solutions to those patients who are not able to use digital or remote services for any reason.